2018
DOI: 10.1002/jso.25236
|View full text |Cite
|
Sign up to set email alerts
|

Bone tumor resection guide using three‐dimensional printing for limb salvage surgery

Abstract: Background and Objectives The three‐dimensional (3D)‐printed bone tumor resection guide can be personalized for a specific patient and utilized for bone tumor surgery. It is noninvasive, eidetic, and easy to use. We aimed to categorize the use of the 3D‐printed guide and establish in vivo accuracy data. Methods We retrospectively reviewed 12 patients, who underwent limb salvage surgery using the 3D‐printed guide at a single institution. To confirm the achievement of a safe bone margin, we compared the actual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 21 publications
0
46
0
2
Order By: Relevance
“…Previous studies have showed that no gaps between the implant and the host bone can significantly improve the stability of the reconstruction . 3D printing technology can allow for more accurate tumor resection and enable precise fitting between implant and residual bone fragments . The functional results allowed patients to return to good limb functions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that no gaps between the implant and the host bone can significantly improve the stability of the reconstruction . 3D printing technology can allow for more accurate tumor resection and enable precise fitting between implant and residual bone fragments . The functional results allowed patients to return to good limb functions.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one study exists that has measured the in vivo accuracy of PSI for tumor resections. 12 The authors retrospectively reviewed 12 patients, who underwent limb salvage surgery using a 3D‐printed guide at a single institution. They compared the actual and planned distances between the cutting surface and tumor, which were reported in the final pathological report.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of printer types are commercially available that differ in technology, cost, materials available, and print time. Although not a quantitative imaging acquisition technique, postprocessing allows for generation of quantitative information that can be used to plan osteotomy sites, select the allograft prosthesis, determine the volume of a surgical defect, and aid in determining surgical reconstruction options for patients with MSK tumors [108][109][110][111][112] (►Fig. 7).…”
Section: Quantitative Presurgical Planning and 3d Printingmentioning
confidence: 99%